Pengembangan Media Pembelajaran Local History dalam Meningkatkan Kesadaran Sejarah Siswa SMA - Herdin Muhtarom; Andi Andi (Universitas Indraprasta PGRI Jakarta, 2023)
The development of teaching materials in technology-based history learning aims to improve the quality of education through the use of technology and increase historical awareness. The use of Local History learning media has an appeal for use in learning local history. Innovation in the use of the Local History application elaborates on the use of technology in learning local history in increasing students' historical awareness. The aim of this research is to develop teaching materials based on local content to increase students' historical awareness through the use of technological development. This study utilized research and development methods. By using a 4D model development research approach (Define, Design, Develop, Disseminate). The results showed that the use of Local History teaching materials using the Likert scale validation test could increase high school students' historical awareness. This is based on the results of the validation test which consists of the Local History application design validation test which shows a result of 100. Then the application teaching material test shows a result of 100. And finally the test of the Local History application on the effectiveness level of application development which shows a result of 100.